Educational Content and Acceptability of Training Using Mobile Instant Messaging in Large HIV Clinics in Malawi - Tom Heller; Sabine Bélard; Odala Sande; Tapiwa Kumwenda; Joe Gumulira; Prakash Ganesh; Salem Gugsa; Hannock Tweya; Sam Phiri (Ubiquity Press, 2021)
Background: In resource-limited settings, many HIV-infected patients with advanced HIV-related disease need specialized care not represented in guidelines. Training opportunities for healthcare providers on advanced HIV care are limited. The aim of this study was to evaluate the educational content and acceptability of mobile instant messaging (MIM) as a training and telemedicine tool for HIV care providers in Malawi. Methods: At the Lighthouse Clinic, Malawi, a MIM group using WhatsApp® was created for clinical officers and moderated by an infectious disease consultant. Questions encountered in the clinics as well as educational cases were posted; identifying data was not to be posted. MIM conversation was analyzed and in-depth interviews with users on its perceptions were performed. Results: MIM was utilized by 25 clinical officers and five physicians with an average of 2.3 threads/week over the observation period of 15 months. Discussed topics related to tuberculosis (25 threads), adverse drug reaction (22 threads), antiretroviral treatment (21 threads), cryptococcal meningitis (12 threads), and drug dosing/logistics. In 20% of the threads at least one image file was shared (mainly pictures of skin conditions and chest X-rays). In-depth interviews showed that clinical officers appreciated MIM group as a telemedicine consulting and training tool. Conclusion: MIM was a successful and well-accepted telemedicine tool for support and training of clinical officers providing HIV care in a resource-limited setting. MIM may be integrated in training strategies to expand the knowledge of HIV care providers.